2017
DOI: 10.1177/0306624x17735055
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Need Profiles of Serious and Chronic Female Juvenile Offenders: Implications for Female Juvenile Correctional Programming

Abstract: Understanding differences and similarities between male and female juvenile offenders is critically important for determining the treatment needs of each group. Less is known, however, about the similarities and differences among female juvenile offenders and the variation in their needs, risks, and psychosocial profiles. Understanding the variation among female juvenile offenders could lead to improvements in gender-responsive interventions and treatment. Latent profile analysis was conducted to construct ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The underlying needs are the central theme throughout the process of rehabilitation because they appear to be important factors contributing to the occurrence of antisocial behaviour, and therefore are possible key motivational factors leading towards prosocial behaviour [16,35]. Overall, it is recommended that treatment programmes for justice-involved female adolescents consider including multidimensional, systemic, and gender-responsive components [60,61]. The current findings suggest public policy and interventions should address the young women's multiple and interacting (criminogenic) needs, such as alcohol/drug use, mental health needs, and trauma exposure [62][63][64], and promote healthy connections with family, peers, school, and the wider community [65,66].…”
Section: Clinical and Policy Implicationsmentioning
confidence: 99%
“…The underlying needs are the central theme throughout the process of rehabilitation because they appear to be important factors contributing to the occurrence of antisocial behaviour, and therefore are possible key motivational factors leading towards prosocial behaviour [16,35]. Overall, it is recommended that treatment programmes for justice-involved female adolescents consider including multidimensional, systemic, and gender-responsive components [60,61]. The current findings suggest public policy and interventions should address the young women's multiple and interacting (criminogenic) needs, such as alcohol/drug use, mental health needs, and trauma exposure [62][63][64], and promote healthy connections with family, peers, school, and the wider community [65,66].…”
Section: Clinical and Policy Implicationsmentioning
confidence: 99%
“…The RNR model is relevant from a risk management perspective because it provides clinicians an effective tool to develop and provide interventions oriented towards solving problems and reducing dynamic risk factors, despite some significant ethical, etiological, and clinical limitations [ 3 ]. In a research study on female justice-involved youth applying RNR principles, Welch-Brewer found four distinct groups/profiles with varying levels of risk-needs—Aggression Only (51%), Alcohol and Drug Use (19%), Socioemotional and Family Relationship Problems (24%), and Severe Alcohol and Drug Use (6%)—all warranting a need for varying levels of treatment intensity and different treatment components across subgroups, ranging from less to more extensive [ 41 , 42 ]. These findings show the variation in risk-need profiles across classes indicates heterogeneity within the sample of female offenders, indicating that the needs of these youth may not be fully met using fixed interventions across the board.…”
Section: Introductionmentioning
confidence: 99%
“…These findings show the variation in risk-need profiles across classes indicates heterogeneity within the sample of female offenders, indicating that the needs of these youth may not be fully met using fixed interventions across the board. The study suggested, for example, that trauma-exposed, female justice-involved youth within the Aggression and Drug Use class, may benefit from cognitive behavioral therapy with a relational approach to better respond to their history of trauma and victimization [ 42 ].…”
Section: Introductionmentioning
confidence: 99%